Prolonged suppression of the anti‐oxidant/anti‐inflammatory effects of BNP post‐Takotsubo syndrome. (29th June 2020) - Liu, Saifei; Ngo, Doan; Chirkov, Yuliy; Stansborough, Jeanette; Chong, Cher‐Rin; Horowitz, John D.
Abstract: Aims: Takotsubo syndrome (TTS) episodes are primarily initiated by 'pulse' release of catecholamines inducing neutrophil infiltration and myocardial inflammation in susceptible individuals (largely ageing women). Evidence of myocardial inflammation and associated energetic impairment persists for ≥ 3 months post‐acute TTS episodes, suggesting the existence of additional 'perpetuating' mechanisms. The effects of B‐type natriuretic peptide (BNP) in suppressing superoxide (O2 − ) release from neutrophils are transiently impaired in acute heart failure. We also evaluated the extent and duration of BNP‐induced suppression of O2 − release post‐TTS. Methods and results: TTS patients were studied acutely ( n  = 34) and 3 months thereafter ( n  = 13) and compared with control subjects ( n  = 25). O2 − generation from neutrophils, triggered by N ‐formyl‐methionyl‐leucyl‐phenylalanine and phorbol myristate acetate, and its suppression by BNP, were measured in vitro . Determinants of variability in BNP effect were sought via univariate and multivariate analyses. Relative to control subjects, in TTS patients, BNP suppression of both phorbol myristate acetate and N ‐formyl‐methionyl‐leucyl‐phenylalanine‐induced O2 − release was impaired acutely ( P  < 0.05 for both); this did not improve over the 3‐month recovery period, despite treatment with conventional anti‐failure medication in 85% of patients. No significant correlates of BNP effect (other than TTS) were identified. Conclusions: (1) While TTS is associated with marked and prolonged release of BNP, there is virtually total loss of the ability of BNP to suppress neutrophil O2 − release and its impact on tissue inflammation. (2) BNP responses do not recover for at least 3 months post‐attacks, suggesting that this might contribute to perpetuation of myocardial inflammation in TTS patients.